Effect of pendant groups on the blood compatibility and hydration states of poly(2‐oxazoline)s. Issue 21 (19th July 2021) - Liu, Shichen; Kobayashi, Shingo; Nishimura, Shin‐nosuke; Ueda, Tomoya; Tanaka, Masaru
Abstract: Poly(2‐methyl‐2‐oxazoline) (PMeOx), poly(2‐ethyl‐2‐oxazoline) (PEtOx), poly(2‐ n ‐butyl‐2‐oxazoline) (PBuOx), and poly(2‐phenyl‐2‐oxazoline) (PPhOx) are selected as poly(2‐oxazoline) (POX) models to study the effect of pendant groups on their blood compatibility and hydration states. A comprehension of this can provide a perspective for understanding the biocompatibility of PMeOx and PEtOx in water‐polymer interactions and may inspire the development of novel blood‐compatible POX derivatives. The aforementioned four POXs are grafted onto glass substrates via photo‐grafting, and their blood compatibility is estimated via platelet adhesion and the degree of denaturation of the adsorbed fibrinogen. The hydration states of the POXs are investigated using differential scanning calorimetry and attenuated total reflection infrared spectroscopy. Intermediate water is found to be present in hydrated PMeOx and PEtOx, but is observed to be scarce in hydrated PBuOx and PPhOx. This could be the reason for the biocompatibility of PMeOx and PEtOx. The carbonyl groups in PMeOx and PEtOx can be fully hydrated. However, in PBuOx and PPhOx, water mainly exists as bulk water. The hydration of the carbonyl groups is hindered by the bulky side chains, and IW cannot be generated. Abstract :